Diel- and temperature-driven variation of leaf dark respiration rates and metabolite levels in rice - Rashid, Fatimah Azzahra Ahmad (The New phytologist, 2020)
© 2020 The Authors. New Phytologist © 2020 New Phytologist Trust.